Rancang Bangun Alat Penjebak Tikus (Mouse Trap) Otomatis Dikontrol Via Iot (Internet Of Things) - Iqbal, Moh; Bachri, Affan; Abidin, Zainal (Universitas Muhammadiyah Jakarta, 2023)
ABSTRAKBagaimana cara membuat alat penjebak tikus (mouse trap) otomatis dikontrol via IOT (internet of things) Bagaimana cara kerja fungsi alat penjebak tikus (mouse trap) otomatis dikontrol via IOT (internet of things) Identifikasi Masalah Pada tahap ini, dilakukan identifikasi permasalahan yang diangkat menjadi penelitian tugas akhir. Proses identifikasi dilakukan melalui penelusuran sistem yang sudah banyak digunakan untuk melakukan pengendalian hama padi. Berdasarkan sistem yang sudah ada dirancang sebuah sistem baru yang sebagai pengembangan dari sistem tersebut.Pengujian alat menggunakan benda mati telah berhasil, alat mampu menjatuhkan target ke dalam bak sesuai dengan yang diharapkan. Setelah menjatuhkan target ke dalam bak maka alat dapat mengirim pemberitahuan ke aplikasi Blynk dan dapat dipantau langsung oleh user Membuat pergerakan servo lebih cepat, karena dengan semakin cepat pergerakannya maka tikus akan semaikn sulit untuk antisipasi kabur dari jebakan, pemilihan servo dapat mempengaruhi kualitas dan tingkat keawetan alat. Alat dapat ditambahi counter masuknya tikus ke dalam bak, selama ini counter hanya dilakukan saat proses menurunnya jungkat jungkit dan tikus sudah dianggap akan masuk ke dalam bak. Kata Kunci : (mouse trap), internet of things,BlynkABSTRACTHow to make the mouse trap automatically controlled via IOT (internet of things) How the function of the mouse trap is automatically controlled via IOT (internet of things) Problem Identification At this stage, identification of the issues raised be a final research project. The identification process is carried out by tracing systems that have been widely used to control rice pests. Based on the existing system, a new system was designed as a development of the system. The testing of the tool using inanimate objects was successful, the tool was able to drop the target into the tub as expected. After dropping the target into the tub, the tool can send notifications to the Blynk application and can be monitored directly by the user Makes the servo move faster, because the faster the movement, the more difficult it will be for mice to anticipate escaping from the trap, servo selection can affect the quality and level of durability tool. The tool can be added with a counter for the entry of rats into the tub, so far the counter is only done when the seesaw descends and the rat is considered to be entering the tub.This tool is made of several main circuits, namely the ATMega328P IC to process data, the HC-SR04 ultrasonic sensor as a proximity sensor, the HC-05 bluetooth module as a connection between devices, the tf-card shield module as a data logger processor, and a buzzer as an indicator. All assembled into a single unit into a tool that can be carried anywhere and in the form of a belt. Based on the results of experiments that have been carried out by comparing the effectiveness and efficiency of the tool with the results of other similar tools, the difference between the two tests of the tool is not much different and is still at the same limitKeywords : (mouse trap), internet of things,Blynk